14x-(6x-3)=59

Simple and best practice solution for 14x-(6x-3)=59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14x-(6x-3)=59 equation:


Simplifying
14x + -1(6x + -3) = 59

Reorder the terms:
14x + -1(-3 + 6x) = 59
14x + (-3 * -1 + 6x * -1) = 59
14x + (3 + -6x) = 59

Reorder the terms:
3 + 14x + -6x = 59

Combine like terms: 14x + -6x = 8x
3 + 8x = 59

Solving
3 + 8x = 59

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 8x = 59 + -3

Combine like terms: 3 + -3 = 0
0 + 8x = 59 + -3
8x = 59 + -3

Combine like terms: 59 + -3 = 56
8x = 56

Divide each side by '8'.
x = 7

Simplifying
x = 7

See similar equations:

| 2(4z+1)-7=59 | | 6[2-(3+4x)]-2x=-8+2(1-13x) | | (2x-2)+(5x-7)= | | X-25/100 | | 2x^2-12x-12= | | 37=29-2(x-1) | | 0.09xX=115.80 | | 8/50= | | w=8s+p | | -16+26=2(x+1) | | .75x+3=x+.5 | | 6/3x-5=3/2x | | 2(x-10)=-8 | | 0.09xX=83.07 | | (-4±√20)/2 | | -9-2x+6x=27 | | 37x+7=6(6x+1) | | 18x-7=14x-23 | | 2x+23y=11 | | y+1.2=2 | | 9x+1.5y=11 | | x+56=-24 | | -10z-0.9=-20z+1.1 | | -9+2+3x=22 | | 2(2x+2)+2(x+34)=312 | | 2x^2+30x+189=0 | | f(n)=9/n | | X/10-x/35=1/10 | | -5.39=logx | | 7x+2=5x+3 | | 6(79-5x)=11(4x-4) | | 180-x=.4(x)+5 |

Equations solver categories